Contemporary Container Security - Gujar, Girish (Palgrave Studies in Maritime Economics,, 2018)
This book belongs to the Port Economics and Global Supply Chain Management strand of the Palgrave Studies in Maritime Economics book series, commissioned by Hercules Haralambides. This book addresses the security of the global system of maritime-based trade, with a focus on container security. Existing discussions about maritime security are almost always tactical, myopic, and fragmented. This book strives to overcome such defects by discussing maritime security from its myriad perspectives - how we should think about it, how we could measure it, and how we can better manage/control it. In this way, the authors examine the ways in which maritime stakeholders can and should work together to build a more secure and resilient global system of maritime trade. .